THE INFLUENCE OF THE HALAL TOURISM CONCEPT AGAINST EMPOWERMENT THE ECONOMY OF CIVIL SOCIETY IN TEBUIRENG JOMBANG. (Study in Gus Dur Tebuireng Jombang Cemetery Area) - Ashlihah Ashlihah; Naily Elmuna (Universitas KH. A. Wahab Hasbullah, 2024)
Abstract The purpose of the study is to describe the implementation of the concept of halal tourism in the tourist attraction of Gus Dur's cemetery area and to determine the influence of the concept of halal tourism both partially and simultaneously on the economic empowerment of civil society in Tebuireng Jombang. This type of research is quantitative. The results of this study shows that: There is an influence of the concept of halal tourism (Ad-din, An-Nafs, Al-